Altimetric and hypsometric analysis for soil and water conservation: A case study of Anjani and Jhiri river basin, Northern Maharashtra, India (2015)
The present paper contains longitudinal profile, hypsometric analysis of river basin and geomorphological studies for future planning of soil and water conservation in Anjani and Jhiri river basin, Jalgaon district, Maharashtra, India (20°45’ to 21°08’N Latitude and 75°09’ to 75°27’E Longitude). The main aim of the present study is to recommend a suitable site for soil and water conservation in Anjani and Jhiri river basin, Northern Maharashtra, India. The study area is geologically covered by Deccan trap basalts of the Cretaceous to the lower Eocene age, and some part is covered by thick alluvium of the Quaternary age. Drainage map of the study area reveals two drainage patterns including dendritic and sub dendritic patterns, indicating that the uniform lithology of the basaltic landforms has uniform resistance to erosion. This condition has caused the Anjani and Jhiri River get little recharge from the rainwater and the surface drainage flows during only monsoon season and latter becomes dry. Therefore, water conservation is a prime need for minimize water scarcity problems in the study area. In the present study, landscape information, such as longitudinal profile and hypsometric integral, has been analysed. The longitudinal profile reveals the presence of nick points at three locations in Anjani river and two locations in Jhiri river. The nick points indicate that the rapids are formed due to different erosion, relief and presence of lineament (Joint).The hypsometric integral values for the Anjani and Jhiri river are 0.52 and 0.51, respectively. The present research illustrates that both basins fall under equilibrium stage and are in a mature phase of development. ResumenEl presente artículo contiene el perfil longitudinal, el análisis altimétrico de las cuencas ribereñas y los estudios geomorfológicos para la planeación a futuro de la conservación de suelos y aguas de los ríos Anjani y Jhiri, en el distrito Jalgaon, Maharashtra, India (20° 45' a 21° 08' N de latitud y 75° 09' a 75° 27' E de longitud). El objetivo principal de este estudio es la identificación de un lugar apropiado para la conservación de agua y de suelos en las cuencas de los Anjani y Jhiri, al norte de Maharashtra. El área de estudio está geológicamente cubierta por basalto de las Traps del Decán, en la era del Cretáceo al bajo Eoceno, y por aluvión espeso de la era Cuaternaria. El mapa hidrográfico de la zona de estudio muestra dos modelos de drenaje, el dendrítico y el subdendítrico, lo que indica que la litología uniforme de los accidentes geográficos basálticos tiene una resistencia uniforme a la erosión. Esta condición ha causado que los ríos Anjani y Jhiri tengan una pequeña recarga proveniente de las aguas lluvias y de los drenajes superficiales durante la única estación monsónica del año y que luego se secan. Es por esto que la conservación del agua es una necesidad primaria para minimizar los problemas de escasez en el área de estudio. En el presente trabajo se analizó la información del paisaje, como el perfil longitudinal y la altimetría integral. El perfil longitudinal revela la presencia de cambios de gradiente en tres puntos del río Anjani y en dos puntos del Jhiri. Los cambios de gradiente indican que los rápidos se formaron debido a la erosión diferente, al relieve y presencia de lineamiento (convergencias). Los valores de altimetría integral para los ríos Anjani y Jhiri son de 0.52 y 0.51, respectivamente. La presente investigación muestra que ambas cuencas se encuentran en un escenario de equilibrio y en una fase madura de desarrollo.